Granular Soil Improvement by Using Polyester Grouts - Celik, Semet; Majedi, Payam; Akbulut, Suat (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
For decades, grouting has been the most popular soil stabilization method. Some additives (especially waste materials) as well as cement and polymeric materials are also widely used as grout mixtures in order to lower costs and achieve the best engineering properties with early strength gain. In this study, unconfined compression and dynamic tests of grouted granular soils were conducted with different mixtures to evaluate the feasibility of using polyester, red mud and micronized clay as grouting materials. The samples were cured for 1, 3 and 7days in order to determine early strength gain. Unconfined compressive strength of all grouted samples has increased with increasing additive percentages and curing time. The damping ratio of all grouted samples has increased with increasing curing time. The overall evaluation of results has revealed that polyester with red mud and micronized clay promising and confer potential as a candidate for grouting applications.
Keywords: Grouting; Granular soil; Polyester; Unconfined compressive strength; Damping ratio; POLYMER CONCRETE; RED MUD; RESIN; MODULUS; Engineering